A Contribution to the Morphology and Phylogeny of Chlamydodon, with Three New Species from China (Ciliophora, Cyrtophoria). (25th September 2017) - Qu, Zhishuai; Pan, Hongbo; Lin, Xiaofeng; Li, Lifang; Aleidan, Abdullah Mohammad A.; Al‐Farraj, Saleh A.; Stoeck, Thorsten; Hu, Xiaozhong
Abstract: Three new cyrtophorian ciliates isolated from coastal areas of China were described based on morphological and genetic data. The Chlamydodon mnemosyne ‐like species Chlamydodon similis sp. n. differs from its congeners mainly by its number of somatic kineties. Chlamydodon oligochaetus sp. n. is distinguished from its congeners mainly by having fewer somatic kineties, and/or an elongated body shape. Chlamydodon crassidens sp. n. is characterized mainly by an inverted triangular body shape, a posteriorly interrupted cross‐striated band (5–6 μm wide), and a large cytostome. Moreover, we provided small‐subunit (SSU) rDNA sequences of C. similis sp. n. and C. oligochaetus sp. n. Maximum likelihood (ML) and Bayesian inference (BI) consistently placed C. similis sp. n. as a sister to C. paramnemosyne, but showed different branching position of C. oligochaetus sp. n., which may be due to a low taxon sampling in the Chlamydodontidae and/or an insufficient resolution of the marker gene at species level.